A Further Study of the Role of Copper in Regard to the Antimutagenic Action of Sodium Copper Chlorophyllin (SCC) in Somatic Cells of Drosophila melanogaster. Issue 8 (January 2013) - Pimentel, Emilio; Cruces, Martha P.; Zimmering, Stanley
Previous findings suggest that copper plays a crucial role in the antimutagenic effect of sodium copper chlorophyllin (SCC). The objective of the current research was to compare the antimutagenic effects of two SCC compounds with different amounts of copper (3.7% and 5.4%, respectively) on the genetic damage induced by gamma rays in somatic cells of Drosophila . Data indicate that an increase in copper content of 31.5% in SCC-5.4 resulted in a greater inhibition of gamma ray genetic damage of 49% whereas only a 2% inhibition with SCC-3.7 occurred. Of greater interest is the association of SCC with a variety of uses in humans, such as a chemo preventive agent and food supplement. A greater attention to the concentration of copper in the SCC product in use should be required.